(untitled) (Revista de Artes Marciales Asiáticas, 2021)
The aim of this study was to investigate the implications caused by the inclusion of karate in the Tokyo 2021 Olympic Games, with regard to Critical Success Factors (FCS) and the development of karate. For this, semi-structured interviews were carried out with athletes, former athletes, coaches and managers with experience in international sport events. The data obtained were analyzed using content analysis and descriptive statistics. The results allowed to conclude that the inclusion of karate in the Olympic Games had effects on the FCS and consequent development of this combat sport. The provision of financial resources for this sport, the participation and organization of national and international competitions, support for athletes, among others, are factors of great relevance in this context. Furthermore, it is expected that this research will provide initial knowledge for those who are interested in the best development of karate and especially the search for international sporting success in this sport, in addition to contributing to other studies related to existing theoretical models or to the specificities of the sport / the context of the interviewees.